KONTRIBUSI PARTAI POLITIK ISLAM DALAM PEMBENTUKAN UNDANG-UNDANG (Studi Atas Pembentukan Undang-Undang Pasca Reformasi) - ', Cahyono; Firdaus, Emilda; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Every independent states certainly forming a law that consider to be inaccord with they are, or extracted of the society in their community. That’s oneof factor law becomes a tool of social engineering. Public’s will to forming alaw was presented in House of People’s Representatives. In fact the Senateoften doesn’t representation of public’s law, but prioritised their concerns.State’s will representation in national politics, which is statementsto appliesnational law and towards of the system formed would be developed.The purpose is :First, Islamic Political Parties contribution to forming alaw since reformation, Second, the extent Islamic Political Parties implicationto forming a law since reformation.The kind of the research is normative legal research, the research basedon the understanding that coherence of the truth, that law is prescriptive andapplied, jurisprudence of research in natural sciences and social sciencescan’t be applied in Legal studies.The conclusion of the research result is hadtwo points. First, formed law is authority House of People’s Representativesbased on 1945’s constitution. Islamic Political Parties contribution to forminga law there’s no regulation about Islamic Political Parties initiative to appliedbecomes Indonesia’s active law. But on process Islamic Political Parties usetheir constitutional rights to arrange their ideology becomes materials ofactive law, although not necessarily accepted. Second, acctually House ofPeople’s Representatives on a par to Islamic Political Parties. IslamicPolitical Parties implicationto forming a lawshow up that the tendency towardsunification of law has led to feuds between state and Muslims. Frictionreflected on some Acts product which caused the dispute between House ofPeople’s Representatives and to Islamic Political Parties in any Laws.KeyWords: Contribution, Party, Politics, Islam, Law, Reform